Three essays on corporate finance - Liu, Yadi (Nanyang Technological University, 2024)
This dissertation includes three essays on corporate finance. Chapter 1 investigates the impact of international mergers and acquisitions (M&A) regulatory frameworks governing non-financial corporations on banks’ stability. By analyzing the implementation of takeover laws in 88 countries, this study reveals a significant increase in bank stability associated with these regulations. Key mechanisms contributing to this stability include enhancements in banks' liquidity and credit risk management. Further analysis indicates that the stabilizing effect of international takeover laws is more pronounced in jurisdictions with stronger creditor rights and superior macroeconomic conditions. This robustness is maintained even when accounting for the impacts of merger waves in the financial and banking sectors. Overall, this paper presents pioneering evidence that M&A legislation leads to an unintended spillover effect, specifically enhancing bank stability by mitigating liquidity and credit risks. Chapter 2 examines the impact of public enforcement on stock price crash risk, utilizing a comprehensive campaign that targeted all listed firms in China. The results indicate that the campaign effectively mitigated stock price crash risk, as evidenced by increased accounting conservatism, enhanced information disclosure quality, reduced positive earnings management, and improved media coverage and analyst recommendations. The analysis further reveals heterogeneous effects influenced by the governance environment and ownership structure, providing additional insights into the inverse relationship between public enforcement and crash risk. Overall, these findings offer significant implications for a comprehensive understanding of the role of public enforcement in mitigating stock price crash risk, contributing a novel perspective to the literature. Chapter 3 investigates the influence of chief executive officers ( CEOs) poverty experiences on their commitment to education donations to support children living in poverty. CEOs who experienced early-life poverty often display greater ethical behavior and empathy towards the disadvantaged than CEOs without such experience. Having experienced poverty, these CEOs are more likely to understand the role of adolescent education in alleviating poverty, especially if they have themselves benefited from education. Using data from the 2016–2020 period on education philanthropy by firms listed on the Shanghai and Shenzhen stock exchanges, we conclude that firms led by CEOs with poverty experiences show superior education donation performance. This effect is further pronounced among CEOs with advanced education. We conduct a variety of endogeneity and robustness tests to enhance the validity of our findings. Overall, our study finds a positive link between CEOs’ poverty experiences and education donations, which is a new insight.